Problem-Based Learning dalam Konteks Blended Learning: Strategi Inovatif untuk Pendidikan Berkelanjutan di Era Pascapandemi - Mira Istiana; Eveline Siregar; Tuti Iriani (Jurnal Kemitraan Masyarakat, 2025)
This systematic literature review examines research trends in problem-based learning (PBL) within blended learning contexts by analyzing 64 peer-reviewed articles from Scopus database published between2020-2024. Using PRISMA methodology, this study identifies key patterns including the dominance of medical education contexts (71.9%), the significant impact of COVID-19 pandemic on pedagogical innovations, and the prevalence of experimental research designs (34.4%). Findings reveal that blended learning emerged as the most researched approach (61%), followed by online/distance learning (23%) and flipped classroom models (11%). The analysis indicates increasing publication trends in 2022 and 2024, with Education Sciences and BMC Medical Education as leading publication venues. This review highlights research gaps in engineering and technology education contexts, limited exploration of long-term learning outcomes, and insufficient mixed-methods studies. These findings provide valuable insights for educators, researchers, and policymakers in designing effective learning strategies that integrate problem-based and blended learning approaches in diverse educational settings.